Polity and culture in the wake of Ayodhya - Deshpande, G. P. (Economic & political weekly, 1993)
In the wake of the destruction of the Babri Masjid (mosque) in Ayodhya on the 6th December 1992, the author explores the phenomenon of communalism, especially pop-Hinduism, and the need of united action against it by the secularists, liberals and leftists of India. He criticizes the lethargy and apathy of the secularists and the liberals. (DÜI-Sen)